We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+5
680
5
avatar

Hi, can anyone solve this problem:

Determine z^n and all values of sqrts with base n of z.  

z=(2-2i)^22 - (-1+isqrt(3))^33 , n=4  

Why is this equality valid 2-2i = 2*sqrt(2)*e^-i*pi/4 = 2^3/2*e^-i*pi/4 ?

 Nov 18, 2015
edited by Guest  Nov 18, 2015
edited by Guest  Nov 18, 2015

Best Answer 

 #3
avatar+105509 
+5

 

Determine z^n and all values of sqrts with base n of z.  

z=(2-2i)^22 - (-1+isqrt(3))^33 , n=4

 

 

 

 

 

\(2-2i\\ = 2(1-i)\\ =2\sqrt2\left(\frac{1}{\sqrt2}+\frac{-i}{\sqrt2}\right)\\ =2\sqrt2\left(cos(\frac{-\pi}{4}+isin\frac{-\pi}{4}) \right)\\ =2\sqrt2e^{i*\frac{-\pi}{4}}\\ =2^{3/2}e^{-\pi/4}\)

 

\((2-2i)^{22}=\left[ 2^{3/2}e^{-(\pi /4)i} \right]^{22}\\ = 2^{33}e^{-(22\pi /4)i}\\ = 2^{33}e^{-(11\pi /2)i}\\ = 2^{33}e^{(-11\pi /2+12\pi/2)i}\qquad \mbox{I added 3 revolutions}\\ = 2^{33}e^{(\pi/2)i}\\ =2^{33}*i\)

 

\(- (-1+i\sqrt3)^{33}\\ =-(-1)^{33}(1-i\sqrt3)^{33}\\ =+(1-i\sqrt3)^{33}\\ =(\sqrt4)^{33}\left(\frac{1-i\sqrt3}{\sqrt{4}}{}\right)^{33}\\ =2^{33}\left(\frac{1-i\sqrt3}{2}{}\right)^{33}\\ =2^{33} \left[cos(-\pi/3)+isin((-\pi/3)i)\right]^{33}\\ =2^{33}\left[ e^{-\pi/3*i} \right]^{33}\\ =2^{33} e^{-11\pi *i} \\ =2^{33} e^{-11\pi *i+12\pi i} \\ =2^{33} e^{\pi i} \\ \)

\(=2^{33}*-1\\ =\;-2^{33}\)

 

 

 

\(z=2^{33}\;i-2^{33}\\ z=2^{33}\;(i-1)\\ ...\\ z^n=2^{33n}\;(i-1)^n\\ ....\\ z^4=2^{33*4}\;(i-1)^4\\ z^4=2^{132}\;(-1-2i+1)^2\\ z^4=2^{132}\;(-2i)^2\\ z^4=2^{132}\;*(-4)\\ z^4=\;-2^{132}\;*2^2\\ z^4=\;-2^{134}\\ z^4\approx \;-2.1778\times 10^{40} \)

 

\(\)

 

\(\)

 

 

(I did the second part first)

 

Why is this equality valid 

2-2i = 2*sqrt(2)*e^-i*pi/4 = 2^3/2*e^-i*pi/4 ?

 

I will add some brackets here.  You should have added the brackets yourself!

2-2i = 2*sqrt(2)*e^(-i*pi/4) = 2^(3/2)*e^(-i*pi/4) ?    I assume that is what you want?

Firstly 

\(2^{3/2}=2^{1+1/2}=2^1*2^{1/2}=2\sqrt2\)

so                     2*sqrt(2)*e^(-i*pi/4) = 2^3/2*e^(-i*pi/4)

Now to show that they are the same as the first part.

i.e.  show that

2-2i = 2*sqrt(2)*e^(-i*pi/4)

 

\(RHS=2*\sqrt2*e^{(-i*\pi /4)}\\ RHS=2*\sqrt2*e^{(-i*\pi /4)}\\ RHS=2*\sqrt2*[cos(-\pi /4)+isin(-\pi /4)]\\ RHS=2*\sqrt2*\left[\frac{1}{\sqrt2}+i*\frac{-1}{\sqrt2}\right]\\ RHS=2*\sqrt2*\left[\frac{1}{\sqrt2}-\frac{i}{\sqrt2}\right]\\ RHS=2(1-i)\\ RHS=2-2i\\ RHS=LHS \)

.
 Nov 18, 2015
edited by Melody  Nov 19, 2015
edited by Melody  Nov 19, 2015
edited by Melody  Nov 19, 2015
edited by Melody  Nov 19, 2015
edited by Melody  Nov 19, 2015
edited by Melody  Nov 19, 2015
 #1
avatar
0

z=(2-2i)^22 - (-1+isqrt(3))^33 , n=4  =-2.17780 × 10^40

 

Why is this equality valid 2-2i = 2*sqrt(2)*e^-i*pi/4 = 2^3/2*e^-i*pi/4 ?

This appears to be FALSE!.

 Nov 18, 2015
 #2
avatar
+5

Not sure what you are asking in the first part.

The equality is correct.

Remember that

\(e^{\imath\theta}= \cos\theta + \imath \sin\theta \)

and that

\(\cos(-\pi/4)=1/\sqrt{2}\),

\(\sin(-\pi/4)=-1/\sqrt{2}.\)

.
 Nov 18, 2015
 #3
avatar+105509 
+5
Best Answer

 

Determine z^n and all values of sqrts with base n of z.  

z=(2-2i)^22 - (-1+isqrt(3))^33 , n=4

 

 

 

 

 

\(2-2i\\ = 2(1-i)\\ =2\sqrt2\left(\frac{1}{\sqrt2}+\frac{-i}{\sqrt2}\right)\\ =2\sqrt2\left(cos(\frac{-\pi}{4}+isin\frac{-\pi}{4}) \right)\\ =2\sqrt2e^{i*\frac{-\pi}{4}}\\ =2^{3/2}e^{-\pi/4}\)

 

\((2-2i)^{22}=\left[ 2^{3/2}e^{-(\pi /4)i} \right]^{22}\\ = 2^{33}e^{-(22\pi /4)i}\\ = 2^{33}e^{-(11\pi /2)i}\\ = 2^{33}e^{(-11\pi /2+12\pi/2)i}\qquad \mbox{I added 3 revolutions}\\ = 2^{33}e^{(\pi/2)i}\\ =2^{33}*i\)

 

\(- (-1+i\sqrt3)^{33}\\ =-(-1)^{33}(1-i\sqrt3)^{33}\\ =+(1-i\sqrt3)^{33}\\ =(\sqrt4)^{33}\left(\frac{1-i\sqrt3}{\sqrt{4}}{}\right)^{33}\\ =2^{33}\left(\frac{1-i\sqrt3}{2}{}\right)^{33}\\ =2^{33} \left[cos(-\pi/3)+isin((-\pi/3)i)\right]^{33}\\ =2^{33}\left[ e^{-\pi/3*i} \right]^{33}\\ =2^{33} e^{-11\pi *i} \\ =2^{33} e^{-11\pi *i+12\pi i} \\ =2^{33} e^{\pi i} \\ \)

\(=2^{33}*-1\\ =\;-2^{33}\)

 

 

 

\(z=2^{33}\;i-2^{33}\\ z=2^{33}\;(i-1)\\ ...\\ z^n=2^{33n}\;(i-1)^n\\ ....\\ z^4=2^{33*4}\;(i-1)^4\\ z^4=2^{132}\;(-1-2i+1)^2\\ z^4=2^{132}\;(-2i)^2\\ z^4=2^{132}\;*(-4)\\ z^4=\;-2^{132}\;*2^2\\ z^4=\;-2^{134}\\ z^4\approx \;-2.1778\times 10^{40} \)

 

\(\)

 

\(\)

 

 

(I did the second part first)

 

Why is this equality valid 

2-2i = 2*sqrt(2)*e^-i*pi/4 = 2^3/2*e^-i*pi/4 ?

 

I will add some brackets here.  You should have added the brackets yourself!

2-2i = 2*sqrt(2)*e^(-i*pi/4) = 2^(3/2)*e^(-i*pi/4) ?    I assume that is what you want?

Firstly 

\(2^{3/2}=2^{1+1/2}=2^1*2^{1/2}=2\sqrt2\)

so                     2*sqrt(2)*e^(-i*pi/4) = 2^3/2*e^(-i*pi/4)

Now to show that they are the same as the first part.

i.e.  show that

2-2i = 2*sqrt(2)*e^(-i*pi/4)

 

\(RHS=2*\sqrt2*e^{(-i*\pi /4)}\\ RHS=2*\sqrt2*e^{(-i*\pi /4)}\\ RHS=2*\sqrt2*[cos(-\pi /4)+isin(-\pi /4)]\\ RHS=2*\sqrt2*\left[\frac{1}{\sqrt2}+i*\frac{-1}{\sqrt2}\right]\\ RHS=2*\sqrt2*\left[\frac{1}{\sqrt2}-\frac{i}{\sqrt2}\right]\\ RHS=2(1-i)\\ RHS=2-2i\\ RHS=LHS \)

Melody Nov 18, 2015
edited by Melody  Nov 19, 2015
edited by Melody  Nov 19, 2015
edited by Melody  Nov 19, 2015
edited by Melody  Nov 19, 2015
edited by Melody  Nov 19, 2015
edited by Melody  Nov 19, 2015
 #5
avatar+105509 
0

 

Finallly I am happy with my answer.  cool

 Nov 19, 2015

28 Online Users

avatar
avatar